Day-ahead Scheduling for a New Wind-CSP Hybrid System. (February 2019) - Yang, Yong; Guo, Su; Liu, Qunming; Li, Rong
Abstract: Increasing level of wind power integration imposes challenges on the power grid due to the variable and intermittent characteristics of the wind resources. Concentrated Solar Power (CSP) plant with low-cost Thermal Energy Storage, is schedulable and controllable, and therefore is an ideal technology to hybridize with wind resources for generation smoothing. Furthermore, an Electric Heater, which converts redundant wind power into thermal energy, can be coupled with CSP plants to both reduce wind curtailment and provide more operational flexibility into power systems. Thus, this paper proposes a new hybrid power generation system integrating wind resources and CSP with an Electric Heater. A mixed-integer linear programming model is established to maximize the daily profit of the hybrid system. In this work, the effects of Electric Heater on the system considering different weather conditions are studied. The results show that the system proposed can effectively mitigate the wind power fluctuation, reduce the wind curtailment, and increase the power dispatchability of the hybrid system.